BIG DATA CAPITALIZATION IN ATTEMPT TO SOLIDIFY TANIHUB STARTUP OPERATIONS: A CASE STUDY - Fakhreza Aminurahman; Lien Herlina; Nur Hasanah, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The high growth of startups in the VUCA (Volatile, Uncertainty, Complexity, Ambiguity) era was offset by the high number of failures of various businesses that relied on the technology. In many industries, the increasing level of vulnerability, uncertainty, and complexity of businesses is undermining the market and changing the nature of competition. Tanihub startup is an e-commerce startup that is considered able to come out as a winner by capitalizing the big data they formulated. This study aims to (1) identify variations in big data owned and formulated by the Tanihub Startup Company during its business, (2) review any big data that can be a sustainable competitive advantage for Tanihub Startup, and (3) formulate the implications regarding big data capitalized by Tanihub Startup Company. This study uses VRIO analysis in determining the big data of a company's competitive advantage and marketing in the formulation of strategies to maintain a sustainable competitive advantage. Big data that has been extracted through the 3 scopes, then processed and analyzed using VRIO (Valuable, Rare, Inimitability, Organize) to determine various variations of big data. Tanihub Startup that can be a competitive advantage for the company. Through the VRIO test results of the big data variations that have been analyzed, formulate 10 big data that can be categorized as a sustainable competitive advantage for the company Startup Tanihub. Then, formulate a market strategy based on these competitive advantages using marketing genius.